Agency costs and innovation some empirical evidence - Francis, Jennifer; Smith, Abbie (Journal of Accounting and Economics, 1995)
This paper examines the empirical relation between corporate ownership structure and innovation. We test the hypothesis that diffusely-held firms are less innovative than firms with either a high concentration of management ownership or a significant equity block held by an outside investor. Overall, the evidence indicates that diffusely-held firms are less innovative along the dimensions we examine: patent activity, growth by acquisition versus internal development, and timing of long-term investment spending. These results are consistent with the conjecture that concentrated ownership and shareholder monitoring are effective at alleviating the high agency and contracting costs associated with innovation.